Physical properties of the tunic in the pinkish-brown salp Pegea confoederata (Tunicata: Thaliacea) - Daisuke Sakai; Hiroshi Kakiuchida; Jun Nishikawa; Euichi Hirose (Zoological Letters, 2018)
Abstract Background Invisibility in the water column is a crucial strategy for gelatinous zooplanktons in avoiding detection by visual predators, especially for animals distributed in the euphotic zone during the daytime; i.e., surface dwellers that do not undergo diel vertical migration. Salps, a member of the subphylum Tunicata (Urochordata), usually have a transparent body that is entirely covered with a cellulosic matrix, called the tunic. Some non-migrator species are known to exhibit a nano-scale nipple array on the tunic surface. However, the physical properties of the salp tunic has been poorly investigated, except for Thetys vagina, in which the tunic was expected to show low reflectance based on the refractive index of the tunic. Pegea confoederata is a non-vertical migrant salp showing pinkish-brown body. We measured the hardness, water content, absorption spectra, and refractive index of its tunic to evaluate its fragility and visibility. Results There are nipple-like protuberances about 80 nm high on the surface of the tunic in P. confoederata. The tunic is very soft; the maximum force to pierce the tunic with a steel rod (1 mm diameter) was < 1 N. The water content of the tunic was > 95%. The absorption spectra of the tunic had no prominent peaks in the wavelength range of 280–800 nm, indicating the tunic is nearly transparent. The difference in refractive indices between tunic and seawater was estimated as 0.002–0.015 at 589 nm. Rigorous coupled wave analyses (RCWA) of light reflection based on 3-dimensional models supported an anti-reflective effect of the nipple array on the tunic surface, which was estimated to vary slightly depending on the forms and the arrangement patterns of nipple-like protuberances in an array. Conclusions The tunic of P. confoederata is very soft and contains more water than those of sessile tunicates (ascidians). Based on the refractive index of the tunic, light reflection is expected to be very low, making this salp’s tunic barely visible in water column. Our results suggest that the nipple array may produce an anti-reflective effect.